Moldova : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This paper reviews economic developments in Moldova during 1995-98. By 1995, the fiscal deficit had been cut to 5 3/4 percent of GDP and annual inflation had fallen to 24 percent. Exports and imports recovered rapidly, with the current account deficit narrowing to 8 1\2 percent of GDP. In 1996, the authorities adopted a three-year program to accelerate and deepen structural reforms and consolidate the stabilization effort. Performance in 1996 and 1997 was mixed. The annual inflation was further reduced to 15 percent at end-1996 and 11 percent at end-1997.